THE QUALITY CHANGES OF FRESH SKIPJACK (Katsuwonus pelamis) DURING CHIILING STORAGE - Raja B. D. Sormin; F. Pattipeilohy; Abraham J. Atua (Pattimura University, 2017)
As a good source of protein and other nutrition that useful for human growth, fish is categorized as perishable food that decaying quickly without good handling. In order to prevent the fish decay and to maintain the quality and freshness of the fish as long as possible, it is need good handling and storage sanitation. Chilling and freezing are the most common technology applied to prolong the shelf life of fresh fish. Chilling is one method of handling that most widely used because it can be practiced easily and quickly. This study aimed to determine the changes in the quality of fresh skipjack (Katsuwonus pelamis) during chilled storage. Parameters as quality indicator measured were total plate count (TPC), total volatile bases (TVB), and pH. Chilled storage were 0, 2and 4days. TPC of fresh skipjack during chilled storage at 0, 2 and 4 days were 1.08 x 102, 8.11 x 102 and 1.06 x 103 cfu/g, respectively. TVB of fresh skipjack during chilled storage at 0, 2 and 4 days were 9.33, 16.00 and 20.00 mgN/100g, respectively. The pH of fresh skipjack during chilled storage at 0, 2 and 4 days was 4.7, 4.8 and 5.4, respectively